STRATEGIES TO IMPROVE THE PERFORMANCE OF MSME’s IN KUNINGAN REGENCY - Wachjuni Wachjuni; Winda Oktaviani; Januar Habibi Mahsyar (Journal of Social Research, 2024)
This study examines the variables of Affiliate Marketing, Viral Marketing, Sales Volume, and Sales Performance. Conducted in Kuningan Regency, West Java, with a population of Micro, Small and Medium Enterprises (MSMEs) in the region, the number of research samples was 160. The type of research used is Quantitative Descriptive with Structural Equation Modelling (SEM) as the analysis model. The results showed a significant influence between Affiliate Marketing and Viral Marketing on Sales Volume. However, there is no significant influence between Affiliate Marketing and Sales Performance. In contrast, Viral Marketing is proven to have a significant influence on Sales Performance. In addition, Sales Volume is shown to have a significant influence on Sales Performance. The findings contribute to practical understanding for MSMEs and related parties in optimising marketing strategies, especially through SEM model analysis. This study also identifies the existence of indirect effects, showing that both Affiliate Marketing and Viral Marketing have an influence on Sales Performance through the intermediary variable of Sales Volume